Femtosecond laser ablation of nitrocellulose for spatio-temporal flow control in µPADs - Builes Münden, Esteban; Dietzel, Andreas (Frontiers in Physics, 2024)
Microfluidic paper-based analytical devices (μPADs) are gaining popularity due to their low cost and ease of use, but controlling fluid flow for more complex biochemical assays within these devices remains challenging. This study investigates femtosecond laser ablation of nitrocellulose (NC), a preferred material for µPADs, to create mechanically switchable barriers and flow controllers. We investigated NC ablation using single laser pulses and spatially overlapping pulses that generate lines. Single pulse ablation thresholds were determined for wavelengths of 1,030 nm, 515 nm and 343 nm. Line ablation characteristics were investigated as a function of the temporal and spatial pulse separation and laser wavelength. High aspect ratio grooves (up to 4.26) were achieved under specific conditions. These grooves can be used to define the spatial separation of the flow in separated microchannels or to form a barrier line perpendicular to the microchannel that can modulate the temporal behavior of the fluid flow. This barrier introduced an additional high flow resistance slowing down the flow or, if it was designed to cut through nitrocellulose at the entire depth, completely stopped the liquid flow. It was further shown that a barrier formed in this way could be switched by mechanically bending the µPAD at the barrier position. The femtosecond laser patterning method presented here provides precise spatio-temporal control not only for flow branching and multiplexing, but also for controlling flow speed and switching flow on and off within the same manufacturing process. Our results open up new possibilities for complex, multi-step assays on µPADs.